Anti-Corruption Policy of the State: Strategies and Methods - SHEDIY, Maria; MERKULOV, Pavel; POTOMSKY, Vadim; SOKOLOV, Vadim; SMIRNOV, Fedor (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018, 2018)
Anti-corruption policy consists in development and realization of various and successive measures of the state and society for elimination (minimization) of the causes and conditions that create and feed corruption in different spheres of life. Taking into account that corruption can expand and change without constant opposition, it is necessary to distinguish the anti-corruption function of the state as one of its basic tasks. The article views the main types of anti-corruption strategies, realized by modern states and determines both positive and negative consequences of their implementation. The article also analyzes the main methods of opposing corruption, applied in state structures, and performs the attempt to evaluate their effectiveness for the Russian Federation from the position of determined regularities of corruption behavior.